PERUBAHAN TRADISI BATAGAK KUDO-KUDO DI NAGARI KOTO VIII PALANGAI KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Almuhyi, Oki Japrinaldi (Pendidikan Sosiologi, 2014)
This research about in Nagari Koto VIII Palangai Batagak kudo-kudo began tofade. This study aims (1) to describe the process of changing the tradition Batagakkudo-kudo and (2) describe the causes of the change Batagak kudo-kudo traditionin Nagari Koto subdistrict Domains VIII Palangai Coastal Southern CoastalDistrict.This study uses the theory of change Neil Smelser. The research is a qualitativestudy using descriptive type. Informants in the study is a community leader whohas knowledge of the tradition Batagak kudo-kudo, as well as some people whohave already done Batagak tradition kudo-kudo. Methods of data collection isdone by the following techniques: (1) the interview, (2) observation, and (3) studythe document.The results of this study indicate that (1) Batagak kudo-kudo is performed tocelebrate the event, and notify everyone that someone would mengatap his houseand the house will soon be occupied. (2) The process of change Batagak kudokudotradition that once people in Batagak kudo-kudo process carried out jointly,but currently only carried out by a course. And also used when a person finishesBatagak kudo-kudo then immediately held a celebration event, but it is now onlyperformed at the time of thanksgiving will occupy the house. (3) the cause of thechange in tradition Batagak kudo-kudo is (a) because many people these days tobuild a house in the form of a shop (store house) which does not use a roof laidkudokudos like a regular house, house shape society today has been influencedby the outside culture, (b) the public is too busy with activities that do not havethe time to invite mamak and the people around him to make the process Batagakkudo-kudo, and (c) Batagak kudo-kudo this takes a long time and adds to the costin the process. So all kinds of work done by artisans. Thus, it can be concludedthat a change in the tradition Batagak-kudo kudos is due to the loss of a sense ofcommunity and mutual cooperation in social life, as well as the cause of thechange is also due to the tradition of the busyness factor and time-consuming inpractice.